2016
DOI: 10.1165/rcmb.2015-0205oc
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a-3p Is a Negative Regulator of Lung Fibrosis by Targeting Myofibroblast Differentiation

Abstract: Although microRNAs (miRs) have been well recognized to play an important role in the pathogenesis of organ fibrosis, there is a lack of evidence as to whether miRs directly regulate the differentiation of myofibroblasts, the putative effector cells during pathological fibrogenesis. In this study, we found that levels of miR-27a-3p were up-regulated in transforming growth factor-b1-treated human lung fibroblasts in a Smad2/3-dependent manner and in fibroblasts isolated from lungs of mice with experimental pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 47 publications
6
49
0
Order By: Relevance
“…Only during the crisis phase, vaccination-protected mice exhibit elevated levels of miR-122-5p, whereas the corresponding levels further decrease in non-vaccinated mice with lethal infections. Similar courses of miRNA expression levels are here found for miR-30a known to be involved in manifestation and resolution of liver fibrosis (Roy et al, 2015), for miR-27a described to be involved in fibrosis (Cui et al, 2016), and for mir-29b known to suppress transcription of genes encoding for extracellular matrix proteins (cf. Table 1) (Roderburg et al, 2011; Lambrecht et al, 2015; Kitano and Bloomston, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Only during the crisis phase, vaccination-protected mice exhibit elevated levels of miR-122-5p, whereas the corresponding levels further decrease in non-vaccinated mice with lethal infections. Similar courses of miRNA expression levels are here found for miR-30a known to be involved in manifestation and resolution of liver fibrosis (Roy et al, 2015), for miR-27a described to be involved in fibrosis (Cui et al, 2016), and for mir-29b known to suppress transcription of genes encoding for extracellular matrix proteins (cf. Table 1) (Roderburg et al, 2011; Lambrecht et al, 2015; Kitano and Bloomston, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, smooth muscle miRNAs, including miR-27a, a smooth muscle miRNA, influence detrusor contractility and the voiding pattern of unrestrained rats [34], and high miR-27a expression was reported to promote renal tubulointerstitial fibrosis [21]. Increasing evidence has shown that miRNAs play an indispensable role in the pathogenesis of organ fibrosis [35]. The endoplasmic reticulum, a major subcellular compartment, is a eukaryotic organelle involved in calcium homeostasis, lipid synthesis, and protein folding and maturation [36].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that miR-27b was down-regulated in fibrotic lungs and fibroblasts from bleomycin-induced mouse pulmonary fibrosis model. In contrast, miR-27a-3p was found to be increased in the fibroblasts isolated from the lungs of the bleomycin-treated mice although the same authors found that miR-27a-3p was decreased in IPF fibroblasts compared to normal lung fibroblasts [15]. Additionally, TGFβ inhibited miR-27b expression in lung epithelial A549 cells [14], but increased miR-27a expression in MRC-5 fibroblasts [15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, miR-27a-3p was found to be increased in the fibroblasts isolated from the lungs of the bleomycin-treated mice although the same authors found that miR-27a-3p was decreased in IPF fibroblasts compared to normal lung fibroblasts [15]. Additionally, TGFβ inhibited miR-27b expression in lung epithelial A549 cells [14], but increased miR-27a expression in MRC-5 fibroblasts [15]. The reasons for these differences remain to be determined, but could be due to the differences in transcription because miR-27a-3p and miR-27b are located in different chromosomes, chromosome19 and chromosome 9, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation